The degree of availability of some of the proposed standards for art education teachers from the point of view of art education supervisors in Jordan - Albibi, Hassan AbedAlnabi Abel-Razzaq (Journal of Educational and Psychological Sciences, 2022)
The current study aimed at identifying the degree of availability of some of the proposed standards for art education teachers from the point of view of art education supervisors in Jordan, and to reveal the significance of differences in the degree of availability of those standards according to the variables of gender, experience and academic qualification. A questionnaire was prepared to measure the availability of some of the proposed standards for art education teachers from the point of view of their supervisors. It included (5) standards and (26) indicators, and their validity and reliability indicators were verified. The study was applied by a comprehensive survey on all (42) members of the study community male and female supervisor. The study concluded that the degree of availability of the proposed standards for art education teachers from the point of view of art education supervisors in Jordan was high, with mean (3.69), the criterion of mastery of basic technical concepts and skills came in the first place and at a high degree, and with mean of (3.88), while the criterion of being able to explain the association of the fields of art education that is based It was taught in society in the last rank, with an arithmetic mean of (3.63), with a medium degree. While it was found that there were differences due to experience in the field of supervision and in favor of those with higher experience. The study recommended the need to take advantage of the study tool in evaluating the performance of art education teachers and to include its criteria in the supervisory model for teacher evaluation.
Keywords: Suggested standards; Art education teachers; Art education supervisors in Jordan